From The Tweets To Street: The Production of #GejayanMemanggil Movement Discourses and Frames - Rizki Ramadhani Nasution (ETTISAL : Journal of Communication, 2021)
On September 23, 2019, the people of Yogyakarta gathered to respond to the call for protest echoed by People Movement Alliance (Aliansi Rakyat Bergerak) on social media through the hashtag #GejayanMemanggil (Gejayan Calling). At least 5000 people had joined in the protest and successfully circulated the demands to the public through social media, making the hashtag the largest social protest in Yogyakarta after the reformation era. Instead of explaining the importance of the role of social media on social movements, this article focuses on how movement discourse is shaped, collective identities and ideological enemies are constructed, demand is invoked, and calls to action are articulated. The qualitative method with social movement framing analysis was employed to examine the meaning of the discourse and framing of the people in the protest movement. The data in this article were retrieved from interviews with the protesters, online observation and desk research. The results indicate that the hashtag produced a set of frames, covering two main orders of discourse – the marginalization of civilians from the decision-making process and the distribution of material focusing merely on some elites. The author contends that the hashtag acts as an inclusive, flexible and leaderless movement.